Diabetic Technology Update Continuous Glucose Monitoring Systems In The Management Of Diabetes Mellitus (Journal of Pharmaceutical Negative Results, 2022)
The term Diabetes technology is used to denote a combination of state-of-the-art hardware, newer devices and intuitive, user-friendly software that helps in the optimal management of diabetes. This term fundamentally includes two categories viz., the administration of insulin through syringes, insulin pens and precision pumps and secondly the accurate estimation of blood glucose through blood glucose monitoring (BGM) or comprehensive continuous glucose monitoring (CGM). The traditional concepts of glucose monitoring have been expanded to include the new parameters of CGM including target in range (TIR), glucose management indicator (GMI), Glycemic variability targets, time in range, time above range and time below range thereby enabling better evaluation of glycemic status and appropriate precision diabetes care. Several glucose monitoring devices including the rtCGM, isCGM and the professional CGM devices have strengthened the armamentarium of the diabetologist. CGM plays an important role in the management of T1DM, some cases of T2DM, diabetes in pregnancy and in cases of diabetes complicated by CKD.